2003
DOI: 10.1172/jci200315737
|View full text |Cite
|
Sign up to set email alerts
|

Paradoxical resistance to diet-induced obesity in UCP1-deficient mice

Abstract: The availability of mice lacking the mitochondrial uncoupling protein UCP1, has provided an opportunity to analyze the relationship between the capacity for energy expenditure and the development of obesity in response to a high-fat, high-sucrose diet. Congenic UCP1-deficient mice on a C57BL/6J genetic background show a temperature-dependent resistance to diet-induced obesity when compared with wild-type mice. This resistance, which occurs at 20°C, is quickly reversed when the ambient temperature is increased … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
116
4

Year Published

2003
2003
2016
2016

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 262 publications
(137 citation statements)
references
References 45 publications
(18 reference statements)
11
116
4
Order By: Relevance
“…A large body of literature links increased dietary fat intake with obesity and cancer progression [59], but it is becoming clear that factors affecting obesity are altered at ST. For example, a UCP-1 knockout mouse model showed deficits in coldinduced non-shivering thermogenesis as expected, but failed to develop the expected obesity phenotype [60,61]. Several groups have now shown that this unexpected lack of the predicted phenotype was because the mice were housed at ST, and when these mice are housed at TT (and are not burning energy through adaptive thermogenesis) they do become obese [61][62][63][64]. This effect of ST on obesity has been observed in other models as well [65][66][67], and it is clear that precise data on the linkage between diet, obesity, and cancer should be re-examined in the context of absence of cold stress.…”
mentioning
confidence: 63%
“…A large body of literature links increased dietary fat intake with obesity and cancer progression [59], but it is becoming clear that factors affecting obesity are altered at ST. For example, a UCP-1 knockout mouse model showed deficits in coldinduced non-shivering thermogenesis as expected, but failed to develop the expected obesity phenotype [60,61]. Several groups have now shown that this unexpected lack of the predicted phenotype was because the mice were housed at ST, and when these mice are housed at TT (and are not burning energy through adaptive thermogenesis) they do become obese [61][62][63][64]. This effect of ST on obesity has been observed in other models as well [65][66][67], and it is clear that precise data on the linkage between diet, obesity, and cancer should be re-examined in the context of absence of cold stress.…”
mentioning
confidence: 63%
“…It is speculated that the absence of adequate amounts of BAT could lead to a severe overweight condition (Vijgen et al 2011;van der Lans et al 2013). However, mice with an inactive Ucp1 gene do not have increased susceptibility to DIO (Liu et al 2003), leading to an alternative interpretation that overall, metabolic efficiency is reduced in individuals with lower levels of UCP1-based thermogenesis (Butler and Kozak 2010). Other studies, with both genetic and surgically generated models of classical BAT insufficiency (Myf5-BMPR1A-KO), suggest the existence of a physiological mechanism to ensure thermoregulation by compensatory browning in WAT (Schulz et al 2013).…”
Section: Brown Adipose Tissuementioning
confidence: 99%
“…Schulz et al (2013) showed that classical BAT is crucial during acute cold challenges, but compensatory brown cells induced in WAT in Myf5-BMPR1A-KO mice (with severe insufficiency of classical BAT) had a critical role in normal body temperature maintenance, particularly in long-term cold exposure (Schulz et al 2013). The induction of brown adipocytes in the inguinal fat of mice with a deficiency in UCP1-based thermogenesis was originally shown by Liu et al (Liu et al 2003). The idea that brown adipocytes, which can be induced in white fat depots by adrenergic signaling, constitute a mechanism for reducing or preventing obesity is still not settled.…”
Section: Brown Adipose Tissuementioning
confidence: 99%
“…As emphasized by Williams and Wagner [92], unexpected consequences of genomic modifications are frequent, and the phenotype or lack of phenotype observed in any transgenic experiment is a function of both the planned genetic modification and of secondary responses of the organism to that perturbation. An example of this principle was demonstrated in the case of UCP1-knockout mice, which when reared at 22 8C (but not at 278C) are more resistant to obesity during high-fat feeding than their wild types [93]; the authors attribute this paradox to alternative, calorically more costly pathways of metabolism for maintaining body temperature in the absence of UCP1-mediated nonshivering thermogenesis. Thus, since the knocking out of genes for reasonably well-established functions often fail to reveal the expected impairment in these functions because of compensatory mechanisms (known or unknown), the failure of UCP2 or UCP3-knockout mice to reveal major impairments in weight regulation via thermogenesis or substrate metabolism is not sufficient to reject the hypothesis that these UCP1-homologues play a role in thermogenesis or lipid metabolism.…”
Section: Is There a Role For Uncoupling Proteins In Fat Metabolism Anmentioning
confidence: 99%